The historical change of the concept of the “image of Lithuania”: from “the one history of barbarism” to “the victim of history” - Aleknonis, Gintaras (Information & Media, 2017)
The concept of the “image of Lithuania” is widely used by different researchers of communication, public relations, management, history or literature. The historical outlook into this concept reveals the lack of common theoretical background. Thus the idea appears to be have a high lack of concept. It is complicated to speak about any common scientific attitudes towards the subject or about a certain school of research. The more comprehensive exploration into the history of “the image of Lithuania” allows us to identify two of the most important trends of research: wide-ranging analyses of the image of the country in the past and a theoretical explanation of modern public relations campaigns which aim to present Lithuania to foreign countries. The short history of the “image of Lithuania” allows us to speak about the image as part of the national identity or national memory. The image could be acknowledged as a part of certain political ambitions or even be a part of the brand of the state. The creation of the image could be understood as a passive observation or as an active campaign. Image creation, dissemination, maintenance and correction could become a profitable business.
Keywords: ...